2018
DOI: 10.1016/j.epsl.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

On mass transport in porosity waves

Abstract: Porosity waves arise naturally from the equations describing fluid migration in ductile rocks. Here, we show that higher-dimensional porosity waves can transport mass and therefore preserve geochemical signatures, at least partially. Fluid focusing into these high porosity waves leads to recirculation in their center. This recirculating fluid is separated from the background flow field by a circular dividing streamline and transported with the phase velocity of the porosity wave. Unlike models for one-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…In geodynamic settings such as mid-ocean ridges, hotspots, subduction zones, or orogenic belts partial melts are generated within the asthenosphere or lower continental crust and ascend by fluid migration within deforming rocks (e.g., Sparks and Parmentier, 1991;Katz, 2008;Keller et al, 2017;Schmeling et al, 2019). Inherent tectonic or rock heterogeneities in such systems may result in spatially varying melt fractions on length scales varying over several orders of magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In geodynamic settings such as mid-ocean ridges, hotspots, subduction zones, or orogenic belts partial melts are generated within the asthenosphere or lower continental crust and ascend by fluid migration within deforming rocks (e.g., Sparks and Parmentier, 1991;Katz, 2008;Keller et al, 2017;Schmeling et al, 2019). Inherent tectonic or rock heterogeneities in such systems may result in spatially varying melt fractions on length scales varying over several orders of magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Melt derived from fertile domains could promote channelization (e.g., Katz & Weatherley, ; Lundstrom et al, ; Weatherley & Katz, ) or magmatic waves. Jordan et al () has shown that solitary magmatic waves may be able to trap and transport geochemical signals in isolation from surrounding melts. Hence, it seems likely that a comprehensive explanation for geochemical variations in erupted basalts should account for both source and transport heterogeneity, and their interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Channels are hypothesized to transport deep, low-degree, enriched melts to the surface without aggregating the depleted melts that are produced at shallower depths (Spiegelman & Kelemen, 2003). Magmatic solitary waves may also be capable of transporting deep, enriched melts in isolation from those produced shallower (Jordan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Porosity waves were suggested to be a fast and efficient fluid transport mechanism forming various focused fluid flow structures (Appold & Nunn, 2002; Barcilon & Richter, 1986; Cai & Bercovici, 2013; Connolly & Podladchikov, 2015; Jordan et al, 2018; Mckenzie, 1984; Räss et al, 2014; Richard et al, 2012; Scott & Stevenson, 1984; Yarushina, Podladchikov, et al, 2015). Most of the previous models ignored the influence of deviatoric stresses on wave propagation, assuming that there is no shear or deviatoric stresses in the rock.…”
Section: Porosity Waves In the Presence Of Shearmentioning
confidence: 99%
“…Porosity waves were suggested to be a fast and efficient fluid transport mechanism forming various focused fluid flow structures (Appold & Nunn, 2002;Barcilon & Richter, 1986;Cai & Bercovici, 2013;Jordan et al, 2018;Mckenzie, 1984;Räss et al, 2014;Richard et al, 2012;Scott & Stevenson, 1984;. Most of the previous models ignored the…”
Section: Porosity Waves In the Presence Of Shearmentioning
confidence: 99%